Enhancing strength and ductility in Ti64 Alloys: Optimizing dual-phase heterostructures and TRIP effects via high-entropy alloy content modulation - Yifeng Xiong; Yuhang Hu; Faming Zhang; Qifa Wan; Yan Chen; Weihao Yuan; Shuo Yin; Caiyun Shang (Materials & Design)
The mechanical performance of Ti-6Al-4 V (Ti64) alloys fabricated via Laser Powder Bed Fusion (L-PBF) can be significantly influenced by the addition of high-entropy alloy (HEA) particles. This study investigates the impact of varying HEA content on the microstructure and mechanical properties of Ti64 alloys. By systematically optimizing the HEA content, a lamellar dual-phase microstructure is achieved. The interplay between the refined α’ martensitic phase and the metastable β phase promotes a progressive transformation-induced plasticity (TRIP) effect, enabling superior strain hardening and stress redistribution. The Ti64-(3.0 wt%) HEA alloy achieves an ultimate tensile strength of 1438.1 MPa and elongation of 9.0 %, representing an optimal balance of strength and ductility.